The BALA project: A pioneering monitoring of Azorean forest invertebrates over two decades (1999–2022) - Gabor Pozsgai; Sébastien Lhoumeau; Isabel R. Amorim; Mário Boieiro; Pedro Cardoso; Ricardo Costa; Maria Teresa Ferreira; Abrão Leite; Jagoba Malumbres-Olarte; Guilherme Oyarzabal; François Rigal; Alejandra Ros-Prieto; et al. (Scientific Data, 2024)
Abstract Globally, there is a concerning decline in many insect populations, and this trend likely extends to all arthropods, potentially impacting unique island biota. Native non-endemic and endemic species on islands are under threat due to habitat destruction, with the introduction of exotic, and potentially invasive, species, further contributing to this decline. While long-term studies of plants and vertebrate fauna are available, long-term arthropod datasets are limited, hindering comparisons with better-studied taxa. The Biodiversity of Arthropods of the Laurisilva of the Azores (BALA) project has allowed gathering comprehensive data since 1997 in the Azorean Islands (Portugal), using standardised sampling methods across islands. The dataset includes arthropod counts from epigean (pitfall traps) and canopy-dwelling (beating samples) communities, enriched with species information, biogeographic origins, and IUCN categories. Metadata associated with the sample protocol and events, like sample identifier, archive number, sampled tree species, and trap type are also recorded. The database is available in multiple formats, including Darwin Core, which facilitates the ecological analysis of pressing environmental concerns, such as arthropod population declines and biological invasions.